DESAIN APLIKASI MAHTEMATICS MOBILE LEARNING BERBASIS ANDROID PADA MATERI TEOREMA PHYTAGORAS - Muhammad Prayoga Mardiana Radita; Puji Nurfauziah (IKIP Siliwangi, 2022)
The use of learning media in schools is still not widely used when the online learning process. This research aims to make the learning medium of Mathematics Mobile Learning application effective and practical as a medium of learning mathematics. The research methods used include three stages of Design Research research methods, in producing a kodular-assisted Android-based Mathematics Mobile Learning application. Mathematics Mobile Learning is packaged in the form of interactive animation, complemented by an evaluation of the understanding of the phytagoras theorem, so that students can personally evaluate the achievement of abilities associated with the phytagoras theorem. Materials presented in the Mathematics Mobile Learning application include learning videos, e-books and practice questions. Mathematics Mobile Learning design trials conducted on Grade VIII junior high students resulted in the growth of student motivation in learning the phytagoras theorem, and students were helped in understanding the material of the Phytagoras theorem. Based on these results it can be seen that the android-based Mathematics Mobile Learning medium is a viable medium, and practical in helping students construct a better understanding of the phytagoras theorem. So that students can learn anytime and anywhere in accordance with the needs of students, besides that it can also be repeated if they do not understand, in contrast to face-to-face learning if you do not understand in the defense it is difficult to repeat again.